(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article is devoted to defining the role of modern education in achieving sustainable development. Particular attention is paid to modern pedagogical technologies, the professional competence of teachers and their impact on the effectiveness of the educational process and the training of highly qualified personnel.